1976
DOI: 10.1288/00005537-197610000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngoesophageal dysphagia and gastroesophageal reflux

Abstract: Pharyngoesophageal dysphagia occurred in 51.3 percent of 1,000 consecutive patients with gastroesophageal reflux. Aspiration, secondary to food obstruction, occurred in 30 percent of these patients, and some developed significant secondary respiratory symptoms. The site of obstruction was localized to the cricopharyngeus by timing the interval from swallow to obstruction. Cricopharyngeal incoordination was demonstrated in 20 of 52 patients studied by high speed esophageal manometry. Surgical correction of gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Dysphagia has been documented in more than 50% of patients with GERD as another frequent laryngopharyngeal symptom. 24 We found dysphagia in 54% of patients with GERD. Nevertheless, the symptoms dysphagia, globus sensation, hoarseness, and laryngospasm seemed not to be specific for reflux disease because the prevalence in non‐GERD patients was even higher than in patients with GERD.…”
Section: Discussionmentioning
confidence: 68%
“…Dysphagia has been documented in more than 50% of patients with GERD as another frequent laryngopharyngeal symptom. 24 We found dysphagia in 54% of patients with GERD. Nevertheless, the symptoms dysphagia, globus sensation, hoarseness, and laryngospasm seemed not to be specific for reflux disease because the prevalence in non‐GERD patients was even higher than in patients with GERD.…”
Section: Discussionmentioning
confidence: 68%
“…While not extensively studied, there are some indications that people with GERD may experience some extraesophageal swallow diculties as well. Henderson et al [19] found a 51.3% occurrence of pharyngoesophageal dysphagia in a sample of 1000 consecutive re¯ux patients. Many of their patients coughed and choked with swallowing because of forward spillage of the obstructed food bolus, and some of them aspirated.…”
mentioning
confidence: 98%
“…It has been dem- onstrated that dihydropyridines act on the calcium channels of nonvascular smooth muscle [25] and may have a role in reducing esophageal spasm [19]. It has also been suggested that treatment of coexisting esophageal disease improves pharyngeal dysphagia, especially when these final effector pathways are intact [26]. It has also been hypothesized that nifedipine has a more global effect, enhancing overall stroke recovery including swallowing during the acute phase [25].…”
Section: Discussionmentioning
confidence: 99%